Don't cosplay with my heart - Castellucci, Cecil 1969- (Scholastic Press, 2018)
Edan Kupferman's life is coming apart: her father is being "sequestered" because the company he works for in Hollywood is in legal trouble, her best friend is in Japan for the summer, and the boy she has a crush on is just plain confusing, so she escapes into the world of comics, and her favorite character, Gargantua...but when Kirk, a boy from her high school, gets her into the sold out ComicCon it starts to look like she might, with a little help, be able to take control of her life after all
Keywords: Comic books, strips, etc -- Congresses -- Juvenile fiction; Comic strip characters -- Juvenile fiction; Characters and characteristics -- Juvenile fiction; Teenage girls -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Families -- California -- Los Angeles -- Juvenile fiction; Cartoons and comics; Characters in literature; Emotional problems; Interpersonal relations; Family life; Los Angeles (Calif.) -- Juvenile fiction; Los Angeles (Calif.); Jugendbuch